Persuasive Sprechhandlungen in Alltagsdialogen des Russischen Unter besonderer Beruecksichtigung ihrer Handlungsbedingungen - Mann, Elke (Specimina philologiae Slavicae, 2000)
Subject of this study are persuasive speech acts in everyday dialogues. Persuasive speech acts are initiated by the will, the opinion, the desire or the feeling of the (linguistic) actor to change the attitudes, opinions, wishes, feelings or actions of the communication partner. By means of persuasive speech acts, the addressee attempts to effect a change of attitude among the addressee without violence, which should cause him or her to execute or refrain from communicative or non-communicative actions. That is, persuasive communication is understood as the attempted influence of the addressee on his future attitudes or future actions.